Autoimmune Associated Diseases in Pediatric Patients with Type 1 Diabetes Mellitus According to HLA-DQ Genetic Polymorphism - Cabezas, Miguel Ángel García; Valle, Bárbara Fernández (IntechOpen, 2011)
None